1981
DOI: 10.1002/jobm.19810210407
|View full text |Cite
|
Sign up to set email alerts
|

The induction of cytochrome P‐450 in Lodderomyces elongisporus

Abstract: In the alkane‐utilizing yeast strain Lodderomyces elongisporus cytochrome P‐450 is induced by aliphatic hydrocarbons and to a lesser degree also by some of their derivatives. Cycloheximide and glucose inhibit the induction process, the former by inhibition of cytoplasmic translation, the latter presumably by catabolite repression. Among the nearly 40 checked compounds tetradecane and 1‐tetradecene are the most effective inducers. The branching of the alkyl chain as well as the terminal introduction of electrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…Normally, C. maltosa also grows well on the terminal and diterminal oxidation products of alkanes, such as l-alkanols (fatty alcohols), fatty aldehydes, fatty acids, m-hydroxy fatty acids, and dicarboxylic acids of the chain length spectrum such as that of the hydrocarbons (Mauersberger et al 1981;Schunck et al 1987a,b;Casey et al 1990;Mauersberger 1991). Shorter chain lengths «C IO ) of these substrates are found to be toxic for yeast cells, or showing inhibitory effects for growth on alkanes.…”
Section: Hydrocarbon and Phenol Assimilationmentioning
confidence: 96%
See 2 more Smart Citations
“…Normally, C. maltosa also grows well on the terminal and diterminal oxidation products of alkanes, such as l-alkanols (fatty alcohols), fatty aldehydes, fatty acids, m-hydroxy fatty acids, and dicarboxylic acids of the chain length spectrum such as that of the hydrocarbons (Mauersberger et al 1981;Schunck et al 1987a,b;Casey et al 1990;Mauersberger 1991). Shorter chain lengths «C IO ) of these substrates are found to be toxic for yeast cells, or showing inhibitory effects for growth on alkanes.…”
Section: Hydrocarbon and Phenol Assimilationmentioning
confidence: 96%
“…Other species names formerly used in the literature for different C. maltosa strains are given with the respective references. Additionally, in some cases publications are given since the strains were renamed into C. Heinritz et al (1981Heinritz et al ( , 1983a,b) Germany (or IMET H128) Voigt (1981,1984) and Schneider and Triems (1981) Stichel et al (1981Stichel et al ( , 1982) (PCK) Schwedt, Germany Wiinsche (1981, 1983) Wiinsche et al (1981) Mauersberger et al (1981, 1984) Riege et al (1981) Glombitza (1982) Gradova et al (1983) Schneider et al (1983) Miiller et al (1982) Brendler et al (1983,b) Voigt et al (1984a,b, 1985) Blasig et al (1984) Bayer et al (1985) Heinritz et al (1985 Candida maltosa Bode andBirnbaum (1984) Golubev et al (1986) Candida maltosa H or H62 Candida Metz and Reuter (1977) Triebel et al (1980) Grirnmecke and Reuter (1980) Briickner and Troger (1981a,b) Kolblin and Birkenbeil (1981) Grirnrnecke and Reuter (1981a,b,c,d) Grirnmecke et al (1981) Kolblin and Troger (1982) Fischer and Reuter (1982) Niiske et al (1982) Rober and Reuter (1982) Candida maltosa H Rober and Reuter (1984a) Candida maltosa 14 Candida maltosa L4 Kunze et al (1984b) Abbreviations: -not determined; C. maltosa -Candida maltosa; C. tropicalis -Candida tropicalis; P. guilliermondii -Pichia guilliermondii; 1. elongisporus -Loddero...…”
Section: History Of Research On Candida Maltosa and On Its Taxonomic mentioning
confidence: 98%
See 1 more Smart Citation
“…For the uptake of alkanes and fatty acids in yeast cells a passive, diffusion-like process is suspected. It was observed that the conversion rate of alkanes and fatty acids greatly depends on the emulsification of the substrate in the medium [10,45,65]. For Y. lipolytica the utilization of hydrophobic compounds by association with hydrocarbon droplets was reported [63].…”
Section: Transport Of Alkanes and Fatty Acid Derivatives 221 Transpmentioning
confidence: 98%
“…This possibility began to be explored in the 1970s (Kaneyuki and Ogata 1975;Kise and Furukawa 1983;Taoka and Uchida 1983). The genes involved in terminal oxidation and their induction were studied, especially in Candida maltosa and in other alkane utilising yeast, and their possible application for ω-oxidation of alkanes or fatty compounds (Mauersberger and Matiashova 1980;Mauersberger et al 1981;Wiedmann et al 1988;Schunck et al 1989;Schunck et al 1991;Ohkuma et al 1995a, b;Ohtomo et al 1996;Zimmer et al 1996aZimmer et al , b, 2000. The first complete genetic engineering work was carried out later by Picataggio et al (1992) who developed an approach with Candida tropicalis.…”
Section: Yeast Route To αω-Dicarboxylic Acidsmentioning
confidence: 99%